Hardness of nano- and microcrystalline lonsdaleite - Huang, Xingshuo; Salek, Alan; Tomkins, Andrew G.; MacRae, Colin M.; Wilson, Nicholas C.; McCulloch, Dougal G.; Bradby, Jodie E. (Applied physics letters, 2023)
Lonsdaleite is a hexagonal allotrope of carbon found in nature in meteorites and at meteorite impact sites. It has been predicted to have an indentation hardness greater than cubic diamond by first principles calculations. However, this has not been demonstrated experimentally. Here, nanoindentation was used to measure the hardness of two different lonsdaleite samples. One contains nanocrystalline lonsdaleite synthesized by high pressure compression of glassy carbon. The other is from a ureilite meteorite that contains lonsdaleite crystals up to ∼1 μm. The hardness of these two samples was determined using both the Oliver–Pharr and Meyer methods. Our results show that the hardness of the lonsdaleite samples is similar to that of diamond; therefore, there is no evidence that these forms of polycrystalline lonsdaleite are significantly harder than similar forms of diamond.